2019
DOI: 10.1128/iai.00482-19
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Innate B1 B Cell Plasmablasts Produce Sustained Granulocyte-Macrophage Colony-Stimulating Factor and Interleukin-3 Cytokines during Murine Malaria Infections

Abstract: The physiopathology of malaria, one of the most deadly human parasitic diseases worldwide, is complex, as it is a systemic disease involving multiple parasitic stages and hosts and leads to the activation of numerous immune cells and release of inflammatory mediators. While some cytokines increased in the blood of patients infected with Plasmodium falciparum have been extensively studied, others, such as granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-3 (IL-3), have not received much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The introduction of 4-HNE adducts in the nascent protein chain during translation and export may also impact on CD 116 export to the membrane, thus resulting in decreased expression and enhanced degradation, a commonly observed event for 4-HNE tagged proteins [ 55 ]. GM-CSF has been reported to increase during malaria infection [ 56 , 57 ]. The cytokine is essential for differentiation of hematopoietic stem cells to erythrocytes, neutrophils, monocytes, eosinophils, and megakaryocytes [ 58 ] and its priming activity on terminally differentiated myeloid cells is well recognised [ 58 , 59 ] and the rationale for inclusion of one plasmid DNA encoding human GM-CSF in a multivalent DNA malaria vaccine [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of 4-HNE adducts in the nascent protein chain during translation and export may also impact on CD 116 export to the membrane, thus resulting in decreased expression and enhanced degradation, a commonly observed event for 4-HNE tagged proteins [ 55 ]. GM-CSF has been reported to increase during malaria infection [ 56 , 57 ]. The cytokine is essential for differentiation of hematopoietic stem cells to erythrocytes, neutrophils, monocytes, eosinophils, and megakaryocytes [ 58 ] and its priming activity on terminally differentiated myeloid cells is well recognised [ 58 , 59 ] and the rationale for inclusion of one plasmid DNA encoding human GM-CSF in a multivalent DNA malaria vaccine [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…As TLR/MyD88 signaling gives rise to VSG-specific antibody induction [56], and TLR signaling appears crucial for maintenance of B cell memory [57,58], CpG DNA has even been proposed as an adjuvant in anti-trypanosome vaccine approaches [59][60][61][62]. Finally, it is worth nothing that IgM + B1 B cells have also been shown to play an important role in malaria-associated antibody production [63] as well as M. tuberculosis associated IgM secretion [64].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Showing that the malfunction of determinants of the immune system corroborate for a higher mortality and susceptibility to cryptococcosis 64 . Therefore, the absence of the B-1 cell component in the XID mice characterizes the loss of cells that are very important for infection resolution 24 , 25 , 38 , 65 , which justify the worsening of the clinical score that has been observed previously using C. neoforomans 66 , and now with C. gattii . We also found that the XID animals still had an extremely deficient serum level of IgM and IgG anti-GXM antibodies, suggesting that antibodies play an important role in infection and act by limiting the spread of yeast.…”
Section: Discussionmentioning
confidence: 86%